2019
DOI: 10.1186/s12885-019-6006-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjunct testosterone on cardiac morphology and function in advanced cancers: an ancillary analysis of a randomized controlled trial

Abstract: Background Adjunct testosterone therapy improves lean body mass, quality of life, and physical activity in patients with advanced cancers; however, the effects of testosterone on cardiac morphology and function are unknown. Accordingly, as an ancillary analysis of a randomized, placebo-controlled trial investigating the efficacy of testosterone supplementation on body composition in men and women with advanced cancers, we explored whether testosterone supplementation could prevent or reverse left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Several proteomic shifts that occurred during CAT were alterations to pathways with known involvement in cardiomyopathy, and despite cardiac muscle being a distinct cell type from skeletal muscle, likely pointed towards similar myopathic processes in skeletal muscle of these patients (Rausch et al, 2021). Nevertheless, it should be noted that an additional ancillary analysis of this study demonstrated that testosterone treatment was associated with improvement in some measures of cardiac function including left ventricular ejection fraction (Scott et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…Several proteomic shifts that occurred during CAT were alterations to pathways with known involvement in cardiomyopathy, and despite cardiac muscle being a distinct cell type from skeletal muscle, likely pointed towards similar myopathic processes in skeletal muscle of these patients (Rausch et al, 2021). Nevertheless, it should be noted that an additional ancillary analysis of this study demonstrated that testosterone treatment was associated with improvement in some measures of cardiac function including left ventricular ejection fraction (Scott et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…In an ancillary study of a randomized controlled trial involving men and women with advanced head-and-neck or cervix cancers, 22 the patients were randomly allocated to receive weekly injections of either 100 mg of testosterone enanthate (6 patients, 1 male) or placebo (10 patients) in addition to receiving standard cancer treatment. After 7 weeks of treatment, testosterone improved left ventricular ejection fraction (LVEF: +6.2% ± 4.3%, vs placebo: −1.8% ± 4.3%; P < 0.05) as well as ventricular–vascular coupling.…”
Section: Testosterone and Cardiac Contractile Functionmentioning
confidence: 99%